Pemakaian Bahasa Indonesia Untuk Penulisan Karya Ilmiah - Tri Indrayanti; Sunu Catur Budiyono; Pana Pramulia; Nur Lailiyah (Universitas Maritim AMNI Semarang, 2024)
Teachers today are not only required to be competent in learning activities, but teachers are also required to be skilled at writing scientific papers. From the competence in writing scientific papers, teacher competence in learning activities will automatically increase, because writing is part of literacy. Writing scientific papers requires continuous practice and also requires good reading competence. Teachers who have reading competence will have writing competence. Ironically, many teachers do not have writing competence, because teachers' reading ability is low. That is why this Community Service activity is carried out. The target of Community Service is the teacher at SMKN 1 Sepulu Bangkalan. Community service is carried out in three stages, namely socialization, training and mentoring. From these three stages, teachers as participants can write scientific papers using good and correct Indonesian.